14C Bomb Peak Analysis of African Elephant Tusks and its Relation to Cites. Issue 5 (October 2019) - Wild, Eva M; Kutschera, Walter; Meran, Annemarie; Steier, Peter
ABSTRACT: We report on a case study of radiocarbon ( 14 C) measurements applied to three pairs of tusks from African elephants, which were supposedly hunted in the 1960s in Tanzania and/or Kenya. The 14 C results of 1.40 to 1.60 F 14 C fall into 14 C bomb peak values between 1960 and 1975, thus confirming the suspected hunting time. Since the trading of ivory from African elephants killed after 1989 was banned by the international CITES convention, the investigated tusks are not affected by this ban.